Strength of Materials / Advanced Theory and Problems: Part II - Timoshenko S (Robert E. Krieger Publishing Company, 1976)
Beams on Elastic Foundations, Beams with Combined Axial and Lateral Loads, Special Problems in the bending of Beams, Thin Plates and Shells, Buckling of Bars and Plates and Shells, Deformations Symmetrical About an Axis, Torsion, Stress Concentration, Deformations Beyond the Elastic Limit, Mechanical Properties of Materials, Author and Subject Index.
Beams on Elastic Foundations, Beams with Combined Axial and Lateral Loads, Special Problems in the bending of Beams, Thin Plates and Shells, Buckling of Bars and Plates and Shells, Deformations Symmetrical About an Axis, Torsion, Stress Concentration, Deformations Beyond the Elastic Limit, Mechanical Properties of Materials, Author and Subject Index.